Tổng hợp và cấu trúc của một số phức chất trans-dicloro(safrol)(amin béo)platin(II). - Chi, Nguyễn Thị Thanh; Đà, Trần Thị; Xưởng, Cao Văn (Vietnam Journal of Chemistry, 2012)
Four complexes of platinum(II) including trans-[Pt(Saf)(methylamine)Cl2] (P1), trans-[Pt(Saf)(ethylamine)Cl2] (P2), trans-[Pt(Saf)(morpholine)Cl2] (P3), trans-[Pt(Saf)(xyclohexyl-amine)Cl2] (P4) have been synthesized. The structure of the complexes have been determinded by elemental analysis, molar conductivity, IR, Raman, electronic and 1H NMR spectra studies.